A Study of a Cavity Nearby a Pulsar at -60º Latitude in the Far Infrared Map - Jha, A. K.; Aryal, B. (Journal of Nepal Physical Society, 2017)
We present physical properties of a region in the interstellar medium where the past evolutionary remnant of pulsar evolution is observed. For this, a systematic search of dust structure in the far infrared (100 μm and 60 μm) IRAS (Infrared Astronomical Satellite) survey was performed using Sky View Observatory. Our selection criteria are as follows: (a) Cavity should be greater than 0.25 degree in diameter and (b) the cavity should have 3-fold minima in flux density. In the 100 micron infrared map, a new cavity-like isolated far infrared dust structure (size ~ 1.62 pc x 0.98 pc) is found at R.A. (J2000) 18h 33m 14.8s and Dec. (J2000) -60° 23' 24". We have studied flux density variation and temperature variation within the structure. We found that the dust color temperature varies from 22.78 K to 24.78 K, with offset of 2 K. The dust mass of each pixel of the region of interest was calculated using their dust color temperature. The excess mass in the region was found to be 1.62 x 1023 Kg. The energy required to create that inhomogeneity in the structure is calculated to be 3.24 x1035 J. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 33-41